Comparison of Histopathologic Findings in Duodenal and Ileal Endoscopic Biopsies in Dogs with Chronic Small Intestinal Enteropathies. (9th February 2013) - Procoli, F.; Mõtsküla, P.F.; Keyte, S.V.; Priestnall, S.; Allenspach, K.
Abstract : Background: The current tendency when investigating dogs with chronic upper gastrointestinal signs is to perform endoscopy and biopsy only the duodenum. This approach could lead to overlooking important ileal lesions and affect the clinical management. Objectives: To compare concurrent duodenal and ileal endoscopic biopsies in dogs with chronic enteropathies and evaluate their correlation with clinicopathologic findings. Animals: Thirty‐eight dogs with chronic enteropathies. Methods: Duodenal and ileal biopsies were retrospectively reviewed. Nine histologic variables, 5 structural (villous stunting, epithelial injury, crypt distension, lacteal dilatation, and mucosal fibrosis) and 4 inflammatory (intraepithelial lymphocytes, lamina propria lymphocytes and plasma cells, eosinophils, and neutrophils) were scored. Clinical severity scores and relevant clinicopathologic variables were evaluated. Results: There was only slight agreement between duodenal and ileal histologic scores (κ = 0.003). There was slight agreement between the presence of any of the morphological and inflammatory variables, with the exception of mucosal fibrosis (κ = 0.44). Statistically significant correlation was found between clinical severity and duodenal crypt distension ( P  = .031), ileal lacteal dilatation ( P  = .038), and ileal mucosal lymphoplasmacytic inflammation ( P  = .035). A significant correlation was found between hypoalbuminemia and ileal lacteal dilatation ( P  = .033) and number of ileal intraepithelial lymphocytes ( P  = .019). A statistically significant correlation was found between hypocobalaminemia and number of ileal intraepithelial lymphocytes ( P  = .012). Conclusions and Clinical Importance: When investigating dogs with chronic upper gastrointestinal signs, the collection of concurrent duodenal and ileal endoscopic biopsies is recommended.